Effect of chronic exogenous oxytocin administration on exercise performance and cardiovagal control in hypobaric hypoxia in rats - Camila Salazar-Ardiles; Carlos Cornejo; Cristobal Paz; Manuel Vasquez-Muñoz; Alexis Arce-Alvarez; Maria Rodriguez-Fernandez; Gregoire P. Millet; Mikel Izquierdo; David C. Andrade (Biological Research)
Abstract Background Outstanding exercise performance has been associated with an exacerbated vagal outflow. Nevertheless, during high-altitude hypobaric-hypoxia (HH), there is a baroreflex-dependent parasympathetic withdrawal and exercise performance deterioration. Notably, vagal control is pivotal in exercise performance, and exogenous oxytocin (OXY) administration has been shown to enhance parasympathetic drive; however, no evidence shows their role in exercise performance during HH. Then, this study aimed to examine the effect of prolonged exogenous oxytocin (OXY) administration on exercise performance during hypobaric hypoxia (HH) in rats. Results A vehicle group (n = 6) and an OXY group (n = 6) performed incremental exercise and baroreflex tests during both normobaric normoxia (NN) and HH (PO2: 100 mmHg, simulated 3,500 m) prior (pre-) and after (post-) 14 days of administration. The results showed that at pre-, there were no significant differences in exercise performance between the two groups, while at post-, the OXY group exhibited similar performance between NN and HH, while the Vehicle group maintained a significant decline in performance at HH compared to NN. At post-, the Vehicle group also demonstrated a reset in the baroreflex and a worse bradycardic response in HH, which was reversed in the OXY group, while the hypoxic ventilatory response was similar in both groups. Conclusion The findings suggest prolonged OXY administration prevents impaired exercise performance and vagal control during short-term HH.